2010
DOI: 10.1186/1471-2288-10-87
|View full text |Cite
|
Sign up to set email alerts
|

A survey of variable selection methods in two Chinese epidemiology journals

Abstract: BackgroundAlthough much has been written on developing better procedures for variable selection, there is little research on how it is practiced in actual studies. This review surveys the variable selection methods reported in two high-ranking Chinese epidemiology journals.MethodsArticles published in 2004, 2006, and 2008 in the Chinese Journal of Epidemiology and the Chinese Journal of Preventive Medicine were reviewed. Five categories of methods were identified whereby variables were selected using: A - biva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A survey of four leading epidemiologic journals found that 20% of the articles published in 2008 used stepwise regression [14]. A study of articles published between 2004 and 2008 in two leading Chinese epidemiology journals found that, of the articles using multiple regression models, 44% used stepwise procedures [15].…”
Section: False Confidence In Stepwise Resultsmentioning
confidence: 99%
“…A survey of four leading epidemiologic journals found that 20% of the articles published in 2008 used stepwise regression [14]. A study of articles published between 2004 and 2008 in two leading Chinese epidemiology journals found that, of the articles using multiple regression models, 44% used stepwise procedures [15].…”
Section: False Confidence In Stepwise Resultsmentioning
confidence: 99%
“…5,7,8 We report the application of lasso shrinkage logistic regression to the analysis of the database described in Orriols and colleagues. Lasso-related methods provide a useful tool, although one that remains unfamiliar to most epidemiologists.…”
mentioning
confidence: 99%
“…As a result, for our analysis we decided to include all hypothesized independent variables of interest in the model without using bivariate analysis or other techniques to screen the variables for best fit. Liao H & Lynn H [6] mentioned, "the screening of variables using significance testing runs the risk of increased type I errors of the predictors in the multivariable model, and should instead be based on evaluation of background knowledge. In addition, using bivariate associations to select variables for multivariable analysis ignores potential confounding or co-linearity between the independent variables, implying that a non-significant variable in the bivariate analysis can in fact be a significant variable in the multivariable analysis".…”
Section: Methodsmentioning
confidence: 99%